Picture Exchange Communication System as a teacher's effort to provide augmentative and alternative modes of communication for children with complex communication needs - Ludfi, Muhammad Kholid Ni'amul; Kamaruddin Nur, Devina Rahmadiani; Sartinah, Endang Pudjiastuti; Kusumawati, Jevie; Romadlona, Nur Alfa Laila; Pamuji, Pamuji; Jannah, Nur (Faculty of Education Universitas Negeri Malang, 2024)
Communication is an important aspect of human life. Communication is needed to carry out social interactions between humans in every social environment. Students also need communication in carrying out their social interactions at school. Students with complex communication needs (CCN) have difficulty communicating with other people, so special school teachers must be able to provide and develop communication skills students with (CCN). If teachers cannot do this, then efforts need to be made so the teachers can provide appropriate services and support accessibility for their students. One form of effort that can be made is by providing training to teachers about the Picture Exchange Communication System (PECS) as augmentative and alternative communication (AAC) for students with CCN. This research describes the training of teachers regarding the implementation of PECS as a means of AAC for CCN. The research used a qualitative case study method, data was collected by observation, interviews and documentation of two teachers who had students with CCN.Data were analyzed using the Miles and Huberman technique. The results show that there is an impact on the teacher's ability to provide communication modes using PECS to CCN students through the training that has been implemented.